Teori relativitas waktu ditinjau dari al-quran surah as-sajadah ayat 5 - Hafidz, Muhammad (Maliki Interdisciplinary Journal, 2024)
This research aims to explore the concept of time dilation in Einstein's theory of relativity, considering perspectives found in the Quran, Surah As-Sajdah, verse 5. The research approach involves the use of web research methods, journal studies, and Quranic exegesis. Both deductive and inductive reasoning techniques are employed to explain the theory, while a comparative technique is used in the analysis, comparing scientific concepts with Quranic concepts in general and interpreting the content of Surah As-Sajdah, verse 5, regarding time relativity. The analysis confirms that the concept of time dilation in this context refers to time relativity or time dilation in Einstein's special theory of relativity. The difference in time measurements is due to the presence of a stationary reference frame as the cause of relativity, an aspect found in the interpretations of commentators on the verse. When a reference frame moves relative to a stationary reference frame, the perceived time will be different, especially when approaching the speed of light.